2019
DOI: 10.1177/0960327119842613
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells pretreated with platelet-rich plasma modulate doxorubicin-induced cardiotoxicity

Abstract: The cardiotoxic adverse effect of doxorubicin (DOX) is the major factor limiting its use. Recently, mesenchymal stem cells (MSCs) have been implicated in the preclinical studies of treatment of DOX-induced cardiotoxicity. The question is MSCs pretreated with platelet-rich plasma (PRP) have a better influence on DOX-induced cardiotoxicity compared to the influence of MSCs alone. Twenty-four Wistar rats were categorized into control, DOX-treated, MSC-treated, and PRP/MSC-treated groups. DOX was injected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 52 publications
0
14
0
1
Order By: Relevance
“…Opened mitochondrial pores lead to mitochondrial cytochrome-C release, and activated caspase-3 triggers proteolytic degradation of cellular components death [127]. Herein, the immunohistochemical staining of myocardial tissues showed that DOX caused an increase in the cleaved caspase-3 and Bax expressions and decreased Bcl-2 expression, which reflected apoptosis's role in DOX-induced cardiomyopathy [76,86,128]. Nevertheless, pre-cotreatment with DPPE reduced cleaved caspase-3 and Bax and enhanced Bcl-2 expressions, implying that DPPE's anti-apoptotic activity could conserve myocardial integrity and mitigate myocardial damage.…”
Section: Discussionmentioning
confidence: 95%
“…Opened mitochondrial pores lead to mitochondrial cytochrome-C release, and activated caspase-3 triggers proteolytic degradation of cellular components death [127]. Herein, the immunohistochemical staining of myocardial tissues showed that DOX caused an increase in the cleaved caspase-3 and Bax expressions and decreased Bcl-2 expression, which reflected apoptosis's role in DOX-induced cardiomyopathy [76,86,128]. Nevertheless, pre-cotreatment with DPPE reduced cleaved caspase-3 and Bax and enhanced Bcl-2 expressions, implying that DPPE's anti-apoptotic activity could conserve myocardial integrity and mitigate myocardial damage.…”
Section: Discussionmentioning
confidence: 95%
“…The investigation revealed hyperemia of interstitial vessels, hyaline degeneration andZenker's necrosis in muscle fibers and mononuclear cell. A study done by Basha and Sujitha, The heart is vulnerable to oxidative stress due to the abundance of mitochondria; the site of basal ROS generation and due to its inherent low antioxidant defenses [51]. Vitamin C is an electron donor, and this is the basis of all its known functions.…”
Section: Discussionmentioning
confidence: 99%
“…Zaki et al, [51] revealed that the modulatory effect of mesenchymal stem cells (MSCs) pretreated with platelet-rich plasma (PRP) on doxorubicin (DOX)-induced cardiotoxicity was superior to the modulatory effect of MSCs alone. The authors mentioned that oxidative stress underlies the DOX-induced cardiotoxicity and accordingly found the oxidant marker MDA to be elevated, while the antioxidant marker SOD decreased in DOX-treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…An improvement of 40.44 m in 6MWT and in NYHA and LVEF groups 95% and 5.25% reduction is observed (3). Moreover, MSC's treated with plateletrich plasma has a greater influence than MSC's alone (12). Vesicles derived from MSC's are used for the treatment of many disorders (13).…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%